Breast milk immune composition varies during the transition stage of lactation: characterization of immunotypes in the MAMI cohort - Rio-Aige, Karla; Fernández-Bargalló, Aina; Vegas-Lozano, Esteban; Miñarro-Alonso, Antonio; Castell, Margarida; Selma-Royo, Marta; Martínez-Costa, Cecilia; Rodríguez-Lagunas, Maria José; Collado, Maria Carmen; Pérez-Cano, Francisco José (Frontiers in Nutrition, 2023)
This is a provisional file, not the final typeset article these results demonstrated the importance of the dynamics of the breast milk composition in terms of immune factors, because even in the same lactation stage, a difference of one week has induced changes in the breast milk immune profile. Moreover, this immune profile does not evolve in the same way in all women. The dynamic compositional changes may be maternal-specific, as we observed differences in parity and exclusive breastfeeding between the two BM immunotype groups, which could potentially impact infant health.